(untitled) (Research, Society and Development, 2020)
Corn and soybean meal are the most used inputs in poultry feed production in Brazil. Changes in the prices of these inputs influence the price and consumption of chicken meat. With this in mind, this work aims to analyse the dynamics of chicken, corn and soybean prices individually and jointly, using the Recurrence Plot method, its extension, the Cross Recurrence Plot and the Recurrence Quantification Analysis, which were developed for the analysis of nonlinear dynamics of temporal series. The data are daily prices for chicken meet, corn and soybeans, from 08/02/2004 to 08/31/2020, provided by the Centro de Estudos Avançados em Economia Aplicada/Escola Superior de Agricultura Luiz de Queiroz/Universidade de São Paulo. The results showed that commodity prices evolve in a similar manner, where soybeans and corn prices are more synchronized with each other than with chicken prices. Considering the input/product relationship it was shown that soybean prices have a greater influence (than corn prices) on the temporal variation of chicken meat prices.